A simple three-degree-of-freedom digital current controller with dead beat response for AC machines - Yuan, Xin (2022)
Since current controllers are implemented digitally, digital current controllers need to be established for pursuing high performance alternating current (AC) machine drives. Considering to enhance the dynamic response, disturbance rejection and stability both, this paper proposes a simple three-degree-of-freedom (3DOF) digital current controller. In the proposed structure, three needed coefficients have been theoretically designed, which stand for the dynamic response ability, disturbance rejection and rejection of the instability caused by machine parameters mismatch, respectively. In addition, the proposed 3DOF current controller can own dead beat response characteristic with one-step delay compensation. Experimental results validate the effectiveness of the proposed digital current controller in a AC machine drive test rig.